DUA MOMEN SAKRAL DALAM ACARA PELANTIKAN PRESIDEN PRABOWO SUBIANTO: HEGEMONI RUANG-WAKTU, PROPAGANDA POLITIK HUMANISME PALESTINA, DAN WACANA KRITIS VAN DIJK - Rafi Ferdiansyah; Soraya Nurfadhilah Devi Chantikha (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2024)
This research aims to read the propagandist messages conveyed in two sacred moments that occurred during the Inauguration of the 8th President and Vice President of the Republic of Indonesia. These two sacred moments occurred when Muzani, as the Chairman of the MPR RI, opened the session and when Prabowo Subianto, as president, delivered a state speech. The sacredness of the two moments was due to the presence of other countries that were not entirely pro-Palestine; some were neutral or even against. This study uses a qualitative descriptive method by utilizing Van Dijk's critical discourse perspective as its study. The results of this study state that the two sacred moments place the other countries present as subjects that are hegemonized in terms of space and time. The speeches delivered in the two moments tend to be humanist political propaganda in responding to the conflict in Palestine. The conclusion in this study is that language is a tool to control, shape perceptions, and influence society through mastery of certain contexts, in this case regarding the concepts of space and time.